Potential Impact of Flow Cytometry Antimicrobial Susceptibility Testing on the Clinical Management of Gram-Negative Bacteremia Using the FASTinov® Kit - Costa-de-Oliveira, Sofia; Teixeira-Santos, Rita; Silva, Ana P.; Pinho, Elika; Mergulhão, Paulo; Silva-Dias, Ana; Marques, Nádia; Martins-Oliveira, Inês; Rodrigues, Acácio G.; Paiva, José A.; Cantón, Rafael; Pina-Vaz, Cidália (Frontiers in Microbiology, 2017)
Laboratory assessment of antimicrobial susceptibility is a prerequisite for adequate management of infections. The aim of this research was to evaluate the performance of the novel FASTinov® kit for antimicrobial susceptibility testing (AST) of Gram negative bacilli directly on positive blood cultures. One hundred and two positive blood cultures from patients of a Portuguese University Hospital were included. AST were performed with routine method, Vitek2, with FASTinov® kit, and with the gold standard microdilution. Bacteria directly extracted from blood cultures were used to inoculate the FASTinov® kit. Time-to-result as well as the number of patients receiving initially inappropriate therapy (and those in whom de-escalation would have been done) and length of stay (LOS) was recorded. Seventy percent of patients were over 70 years old and 18.6% were admitted in intensive care units. Regarding the isolates, 88.2% were Enterobacteriaceae, 9.8% Pseudomonas spp. and 1% Acinetobacter spp. Extended spectrum β-lactamases producing-Enterobacteriaceae were found in 7.8% of cases and 10.8% were multi-drug resistant. Fifty-one hours was the mean of time-to-result for routine test (Vitek2) versus 2 hours response regarding Fastinov® test. The overall agreement between FASTinov® and the reference microdilution method was 98%. According to the susceptibility phenotype, 16.7% of patients received initially inappropriate therapy and the mean hospital LOS of these patients was significantly higher. FASTinov® kit revealed an excellent correlation with the AST standard method and provided much earlier results than Vitek2.